Central breathing abnormalities in children with trisomy 21: Effect of age, sex, and concomitant OSA. Issue 2 (14th December 2020) - Naime, Samira; Weiss, Miriam; Lew, Jenny; Aziz, Julia; Pan, Qi; Allen, Michelle; Xuchen, Xilei; Weinstock, Jered; Nino, Gustavo
Abstract: Background: Trisomy 21 (TS21) is a condition with a high risk for sleep apnea. In the pediatric population, the risk also includes central breathing disorders. The aim of this study was to define the clinical and polysomnographic characteristics of central apnea in infants, children, and adolescents with TS21. Methods: Retrospective review of baseline polysomnograms (PSGs) in children with TS21 in the sleep center at Children's National Medical Center in Washington DC. Results: We included a total of 158 infants, children, and adolescents (0–18 years) with TS21 in this study. The median age was 4.82 years and 62% were male. The primary findings of the study are that (1) 12% of all pediatric subjects with TS21 included had a central apnea index (CAI) > 2/h; (2) the proportion of TS21 individuals with central breathing abnormalities progressively decreased with age being common in young individuals (≤2 years of age) but rare after 10 years of age; (3) additional sleep breathing disturbances (e.g., OSA and/or hypoxemia) are often present in children with TS21 and central apnea; and (4) the prevalence of central breathing abnormalities in TS21 is influenced by sex, being more likely to persist beyond early childhood (>2 years of age) in females than in males. Conclusion: Central breathing abnormalities are common in TS21 among young children (≤2 years of age) and in females older than 2 years of age. Central apnea is often associated with concomitant obstructive sleep apnea and/or hypoxemia in children with TS21.